(untitled) (Spectrum Journal of Innovation, Reforms and Development, 2024)
The development of communicative competence is crucial for vocational school students as it enhances their ability to effectively interact in a professional environment. This article presents a comprehensive methodology aimed at improving students’ communicative competence through enhanced preparation for their future professional activities. The methodology incorporates various pedagogical approaches, strategies, and techniques to ensure the successful integration of communication skills within vocational education.